Comparison of embodied energy and carbon dioxide emissions of brick and concrete based on functional units - Sazedj, Soheyl (2015)
Building materials have different consumption patterns of energy and emissions of carbon dioxide during their production. These differences result from the treatment of the raw materials and the techniques applied to production. Subsequently on an environmental classification one wonders what kind of constructive solution becomes more benevolent to the environment. Masonry building technique has made a comeback as an alternative to conventional reinforced concrete structures with ceramic blocks for closing the spans. The present study refers to the environmental comparison of these two systems. As the definition of functional unit has been introduced to facilitate the comparison of different existing alternatives, the walls are chosen as the functional units, for different building plans and conditions. The comparison considers the most important environmental parameters, i.e. the embodied energy and the carbon footprint. Results obtained indicate that masonry-building walls have a lower embodied energy and carbon footprint compared to those of conventional building. The differences vary with the length of the walls, but are over 22% and reach some 55%. It is hoped that the different wall types considered will enable the comparison of the two options for real application.